The Relationship Between Surgeons Communication and Patients Understanding in Jemursari Islamic Hospital Surabaya - Widhatama, Ega; Satriya Wibawa, Dayu; Chasanatusy Syarifah, Mustika (Jurnal Medis Islam Internasional, 2020)
Communication is a human activity to be able to understand a message between communicators and communicants. Ordinary communication ends with a result called the communication effect. Communication usually occurs with the same meaning in a conversation. Understanding can be defined as the ability to be able to correctly explain the object to be known, and be able to interpret the material correctly. This study aims to determine the relationship between surgeon communication and patient understanding in the hospitalized surgery room at Jemursari Islamic Hospital Surabaya. This research uses a consecutive sampling technique based on sample criteria. The population was all surgical patients who were going to perform surgery and samples were obtained according to the inclusion and exclusion criteria. The sample size is 65 samples and the research instrument was a questionnaire. The results of this study were obtained (36%) respondents communicated ineffectively and (64%) communicated effectively. Besides that, (45%) respondents did not understand what the doctor explained, and (55%) understood what was explained. Analysis using test Chi- Square obtained a very significant relationship between surgeon communication with patient understanding with p-value = 0.000.